Trend and enhanced surveillance of Monkeypox during COVID-19 pandemic in Nigeria - Lateefat K. Amao; David I. Olatunji; Gordon Igbodo; Solomon C. Okoli; Ifeanyichukwu Amaechi; Muhammad I. Goni; Odianosen Ehiakhamen; Olaolu Aderinola; Adesola Ogunleye; Oladipo Ogunbode; Adesola Adeleye; Tajudeen Arowolo; et al. (AOSIS, 2022)
Monkeypox (MPX) is a viral zoonosis with lesions like smallpox. Though rare in Nigeria, sporadic outbreaks have been reported in 17 states since September 2017. Unfortunately, the COVID-19 pandemic has further reduced surveillance and reporting of MPX disease. This study seeks to assess the effect of an enhanced surveillance approach to detect MPX cases and measure the cumulative incidence of MPX in priority states in Nigeria. We identified three priority states (Rivers, Delta and Bayelsa) and their Local Government Areas (LGAs) based on previous disease incidence. We also identified, trained, and incentivized community volunteers to conduct active case searches over three months (January to March 2021). We supported case investigation of suspected cases and followed up on cases in addition to routine active surveillance for MPX in health facilities and communities. Weekly and monthly follow-up was carried out during the same period. Out of the three states, 30 hotspots LGAs out of the 56 LGAs (54%) were engaged for enhanced surveillance. We trained three state supervisors, 30 LGA surveillance facilitators and 600 Community informants across the three priority states. Overall, twenty-five (25) suspected cases of MPX were identified. Out of these, three (12%) were confirmed as positive. Enhanced surveillance improved reporting of MPX diseases in hotspots LGAs across the priority states. Extension of this surveillance approach alongside tailored technical support is critical intra and post-pandemic.